Non-contact Sleep/Wake Monitoring Using Impulse-Radio Ultrawideband Radar in Neonates - Lee, Won Hyuk; Kim, Seung Hyun; Na, Jae Yoon; Lim, Young-Hyo; Cho, Seok Hyun; Cho, Sung Ho; Park, Hyun-Kyung (Frontiers in Pediatrics, 2021)
Background: The gold standard for sleep monitoring, polysomnography (PSG), is too obtrusive and limited for practical use with tiny infants or in neonatal intensive care unit (NICU) settings. The ability of impulse-radio ultrawideband (IR-UWB) radar, a noncontact sensing technology, to assess vital signs and fine movement asymmetry in neonates was recently demonstrated. The purpose of this study was to investigate the possibility of quantitatively distinguishing and measuring sleep/wake states in neonates using IR-UWB radar and to compare its accuracy with behavioral observation-based sleep/wake analyses using video recordings. Methods: One preterm and three term neonates in the NICU were enrolled, and voluntary movements and vital signs were measured by radar at ages ranging from 2 days to 27 days. Data from a video camcorder, amplitude-integrated electroencephalography (aEEG), and actigraphy were simultaneously recorded for reference. Radar signals were processed using a sleep/wake decision algorithm integrated with breathing signals and movement features. Results: The average recording time for the analysis was 13.0 (7.0−20.5) hours across neonates. Compared with video analyses, the sleep/wake decision algorithm for neonates correctly classified 72.2% of sleep epochs and 80.6% of wake epochs and achieved a final Cohen’s kappa coefficient of 0.49 (0.41−0.59) and an overall accuracy of 75.2%. Conclusions: IR-UWB radar can provide considerable accuracy regarding sleep/wake decisions in neonates, and although current performance is not yet sufficient, this study demonstrated the feasibility of its possible use in the NICU for the first time. This unobtrusive, noncontact radar technology is a promising method for monitoring sleep/wake states with vital signs in neonates.